HGX: The anatomy of high growth exporters - Stjepan Srhoj; Alexander Coad; Janette Walde (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2022)
Export boosting is a policy agenda in developed and developing countries. Previous work has found that a small number of Superstars contribute disproportionally to the economy's overall exports. Differently from Superstars, this study is the first to define high growth exporters (HGXs), provide their economic importance and depict their micro-level anatomy. By tracking HGXs in Croatia for over a quarter of a century, 44 out of 100 Superstars in 2019 were previously HGXs. Industry-wise, HGXs are concentrated in manufacturing, information and communication technology, transportation and storage sectors. HGXs are located in higher export active regions, neighboring advanced markets. HGXs represent only 0.5% of all firms and 18% of high growth firms (HGFs) in the economy, but are responsible for about 25% of new exports, and 5% of new jobs. During their growth episode, HGXs hire more employees from technology intensive industries with previous experience in exporting. They often hire on a single year work contract, and more frequently send new employees to work abroad. HGXs have the highest number of new products, and the concentration of HGXs' main export products decreases over time, thus, the growth is driven by multiple products and the simultaneous increase in the number of new export markets. HGXs export to closer markets than Superstars, but to more distant markets than other HGFs and exporters who tend to be more active in less developed markets. HGXs tend to increase their presence in the EU Single Market, introduce new products and substantially increase their unit price.
Keywords: F2; D22; L1; 330; exporting; firms; high growth firms; high growth exporters